Analisa Evaluasi Sistem Pembelajaran Online Di SMK Budhiwarman 1 Jakarta Menggunakan Metode AHP - arizona, fredy; Yana, Adelia Alvi (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2021)
Covid 19 is an epidemic that is hitting right now, in the midst of the covid 19 pandemic, the government issued a policy to study from home, the online learning system has a large number of problems, this is what makes students unable to follow learning optimally. The problems experienced both in terms of facilities, the internet as well as in terms of assignments and the environment, are the cause of students being unable to follow lessons optimally, SMK Budhiwarman 1 is one of the schools where students feel the impact of online learning, the purpose of this research is to conduct a survey to be able to measure how much influence the problems experienced have on student scores, in addition to testing the current system. AHP is a method that allows to measure the level of problems experienced during online learning and can provide ratings to find out the main problems faced. By combining surveys with AHP, it is found that the main problems that are most often experienced are from the internet and from the facilities used for learning, this proves that AHP can be the main method for finding the main problems of the many problems of the online learning system..